2003
DOI: 10.1111/j.1464-410x.2004.04566.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of penile curvature with Essed‐Schröder tunical plication: aspects of quality of life from the patients’ perspective

Abstract: RESULTSOf the 50 patients, 22 had a congenital penile deviation and 28 Peyronie's disease. In all patients the penis was completely straightened. The proportion of patients capable of sexual intercourse was significantly higher after surgery (90%) than before (62%). The frequency of pain during intercourse was halved. Of the 50 patients, 60% would have the same operation again, 32% were undecided and 8% would not; 22% were dissatisfied with the results. None of the patients had complete erectile dysfunction af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 18 publications
0
28
0
4
Order By: Relevance
“…19,33 To enable recommendation of the best surgical approach, there is still a need for long-term evaluations especially with regard to quality of life. 13,19,34 In the present study, we evaluated pre-and perioperative data and self-reported long-term results of patients who underwent surgery for penile correction either by shortening techniques (ST group) or a grafting procedure with TachoSil (TM group). Both groups were similar regarding age, comorbidities, preoperative treatment and erectile function, except for a higher preoperative deviation angle and a higher incidence of plaques in TM group patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,33 To enable recommendation of the best surgical approach, there is still a need for long-term evaluations especially with regard to quality of life. 13,19,34 In the present study, we evaluated pre-and perioperative data and self-reported long-term results of patients who underwent surgery for penile correction either by shortening techniques (ST group) or a grafting procedure with TachoSil (TM group). Both groups were similar regarding age, comorbidities, preoperative treatment and erectile function, except for a higher preoperative deviation angle and a higher incidence of plaques in TM group patients.…”
Section: Discussionmentioning
confidence: 99%
“…Paprastai varpos kreivumas būna nedidelis -iki 15 o ir nesukelia jokių simptomų ar nemalonumų. Kita vertus, didelio laipsnio (30 o -90 o ) varpos kreivumas erekcijos metu gali apsunkinti lytinio akto atlikimą, dėl sudėtingo varpos įvedimo į makštį ir lemti dideles psichologines problemas, sutrikdyti psichoseksualį individo vystymąsi [4]. Kai ligonis skundžia-si šiais simptomais, taikomas chirurginis gydymas.…”
Section: įVadasunclassified
“…Van Der Horst and colleagues reported that 74% of patients complained of subjective loss of length with the Essed-Schröder technique [Van Der Horst et al 2004]. Syed and colleagues reported that after undergoing the Nesbit procedure 50% of patients noticed no change in penile length, 38.1% of patients felt they had a shorter penis but that this did not preclude intercourse, while another 11.9% had shortening severe enough that successful intercourse was impossible [Syed et al 2003].…”
Section: Loss Of Penile Lengthmentioning
confidence: 99%
“…As with all surgeries for PD deformity, there is an incidence of recurrence or persistence of curvature [Andrews et al 2001;Syed et al 2003] Recurrent curvature requiring reoperation 0-20% [Leonardo et al 2012;Van Der Horst et al 2004, Andrews et al 2001Baskin and Lue, 1998] Worse erectile dysfunction 0-6% [Van Der Horst et al 2004;Gholami and Lue, 2002] Change in penile sensation 6-75% [Gholami and Lue, 2002;Syed et al 2003;Leonardo et al 2012] Palpable suture knots (using nonabsorbable suture) 50-100% [Van Der Hors et al 2004;Baskin and Lue, 1998;Leonardo et al 2012] Sutures interfering with intercourse 0-10% [Syed et al 2003;Baskin and Lue, 1998] after plication procedures. The acceptable degree of curvature varies among surgeons and patients.…”
Section: Recurrent and Persistent Curvaturementioning
confidence: 99%